LMD-02. Cerebrospinal Fluid Diversion for Metastatic Leptomeningeal Carcinomatosis: Palliative, Procedural and Oncologic Outcomes. (9th August 2021) - Bander, Evan D; Yuan, Melissa; Reiner, Anne S; Garton, Andrew; Panageas, Katherine S; Brennan, Cameron W; Tabar, Viviane; Moss, Nelson S
Abstract: Background: Leptomeningeal disease (LMD) occurs in 3–5% of patients with solid metastatic tumors and often portends a severe prognosis including symptomatic hydrocephalus and intracranial hypertension. Cerebrospinal fluid (CSF) shunting can provide symptomatic relief in this patient subset; however, few studies have examined the role of shunting in the palliation, prognosis and overall oncologic care of these patients. Objective: To identify and evaluate risk factors associated with prognosis after CSF diversion and assess surgical, symptomatic and oncologic outcomes in this population. Methods: A retrospective study was conducted on patients with solid-malignancy LMD treated with a shunt at an NCI-designated Comprehensive Cancer Center between 2010–2019. Results: One hundred and ninety patients with metastatic LMD underwent CSF diversion. Overall survival was 4.14 months from LMD diagnosis (95%CI:3.29–4.70) and 2.43 months (95%CI:2.01–3.09) from shunting. KPS at time of shunting and BrM number at LMD diagnosis demonstrated significant associations with survival (HR=0.66; 95%CI[0.51–0.86], p=0.002; HR=1.40; 95%CI[1.01–1.93] per 10 BrM, p=0.04, respectively). Eighty-three percent of patients experienced symptomatic relief, and 79% were discharged home or to rehabilitation facilities post-shunting. Post-shunt, 56% of patients received additional systemic therapy or started or completed WBRT. Complications included infection (5%), symptomatic subdural hygroma/hematoma (6.3%), and shunt externalization/removal/repair (8%). Abdominal seeding was not identified. Conclusions: CSF diversion for LMD with hydrocephalus and intracranial hypertension secondary to metastasis can achieve symptomatic relief, hospital discharge, and return to further oncologic therapy, with a complication profile unique to this pathophysiology. However, decision-making in this population must incorporate end-of-life goals of care given limited prognosis.